Pengaruh Tari Kreasi Terhadap Perkembangan Motorik Kasar Anak Usia 5-6 Tahun Di Taman Kanak-Kanak - Novera Dwi Puspita; Hendi Kariyanto (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
This study aims to examine the impact of creative dance on the gross motor development of children aged 5-6 years at TK Aisyiyah Bustanul Athfal Cabang Jarai. Gross motor development is a crucial aspect of child growth, involving the ability to control large body movements such as running, jumping, and dancing. Creative dance, which combines free movements with a certain structure, is considered to provide good stimulation for children's gross motor development. This research employs a quasi-experimental method with a pretest-posttest control group design. The study sample consists of 30 children divided into two groups: an experimental group that participates in the creative dance program and a control group that does not. Data collection was conducted through observation and gross motor tests before and after the intervention. The results show a significant improvement in the gross motor skills of children who participated in the creative dance program compared to the control group. Statistical analysis using the t-test indicates a p-value of less than 0.05, suggesting that the creative dance program has a positive effect on children's gross motor development. Thus, it can be concluded that creative dance is effective in enhancing the gross motor skills of children aged 5-6 years. This study recommends integrating creative dance programs into early childhood education curricula as a way to support optimal physical development in children.